Application of plastic conjugated materials in the repair of sports injury - Li, Peng; Zhou, Jihe (Frontiers in Chemistry, 2023)
For professional athletes or fitness crowd who often participate in sports, sports injury are more common. However, the traditional repair materials for sports injury have many problems, such as long recovery period and poor repair effect. In recent years, many studies have found that conjugated materials have good stability, small side effects and other excellent characteristics, and conjugated materials are used in sports injury repair materials. In order to study the repair effect of conjugated materials on sports injury tissues, this paper prepared nitrogen porphyrin conjugated organic skeleton materials with pyrrole and p-benzaldehyde as substrates, used chemical synthesis and selective laser sintering technology to form plastic conjugated scaffold materials with polyvinyl alcohol, polylactide and conjugated materials, and established mechanical properties and constitutive formula to evaluate the performance characteristics of repair materials. In order to test the effect of plastic conjugated materials on sports injury, experiments were carried out from the aspects of degradability, mechanical properties of repair materials, repair effect of radius defect and new bone formation area. Experimental data: The proportion of newly formed bone area at weeks 3, 6, and 9 using this method was 32%, 52%, and 68%, while the proportion of newly formed bone area at weeks 3, 6, and 9 using traditional methods was 12%, 18%, and 23%, indicating that this method had better bone repair effects than traditional methods. The research in this paper provided a new idea for the application of plastic conjugated materials in the field of sports medicine.